Building and validating a prediction model for paediatric type 1 diabetes risk using next generation targeted sequencing of class II HLA genes. Issue 8 (15th September 2017) - Zhao, Lue Ping; Carlsson, Annelie; Larsson, Helena Elding; Forsander, Gun; Ivarsson, Sten A.; Kockum, Ingrid; Ludvigsson, Johnny; Marcus, Claude; Persson, Martina; Samuelsson, Ulf; Örtqvist, Eva; Pyo, Chul‐Woo; et al.
Abstract: Aim: It is of interest to predict possible lifetime risk of type 1 diabetes (T1D) in young children for recruiting high‐risk subjects into longitudinal studies of effective prevention strategies. Methods: Utilizing a case‐control study in Sweden, we applied a recently developed next generation targeted sequencing technology to genotype class II genes and applied an object‐oriented regression to build and validate a prediction model for T1D. Results: In the training set, estimated risk scores were significantly different between patients and controls ( P  = 8.12 × 10 −92 ), and the area under the curve (AUC) from the receiver operating characteristic (ROC) analysis was 0.917. Using the validation data set, we validated the result with AUC of 0.886. Combining both training and validation data resulted in a predictive model with AUC of 0.903. Further, we performed a "biological validation" by correlating risk scores with 6 islet autoantibodies, and found that the risk score was significantly correlated with IA‐2A (Z‐score = 3.628, P  < 0.001). When applying this prediction model to the Swedish population, where the lifetime T1D risk ranges from 0.5% to 2%, we anticipate identifying approximately 20 000 high‐risk subjects after testing all newborns, and this calculation would identify approximately 80% of all patients expected to develop T1D in their lifetime. Conclusion: Through both empirical and biological validation, we have established a prediction model for estimating lifetime T1D risk, using class II HLA. This prediction model should prove useful for future investigations to identify high‐risk subjects for prevention research in high‐risk populations.